Functional mechanism on stem cells by tea (Camellia sinensis) bioactive compounds - Yao Cheng; Jiachen Sun; Hui Zhao; Hongxing Guo; Jianying Li (Food Science and Human Wellness)
Camellia sinensis (tea), one of the most popular commercial crops, is commonly applied in all parts of the world. The main active ingredients of tea include polyphenols, alkaloids, polysaccharides, amino acids, aroma and volatile constitutes, all of which are potentially responsible for the activities of tea. Stem cells (SCs) are the immature and undifferentiated cells by a varying capacity for proliferation, self-renewal and the capability to differentiate into one or more different derivatives with specialized function or maintain their stem cell phenotype. Herein, a thorough review is conducted of the functional mechanism on SCs by tea bioactive compounds.